TINJAUAN PERJANJIAN SEWA-MENYEWA MENURUT HUKUM ISLAM - KUSUMAWARDHANI, RR ESTI DIAH (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
Abstract  Leasing is one of the most important parts of human economic and social needs because it can support living standards. However, sometimes leasing transactions cause disputes if not done transparently by both parties.Whereas the form of rent that is not permitted in Islam There is a muzara'ah which is commonplace in the time of the Prophet, but by him it is prohibited because there are elements of deception and obscurity which result in disputes and conflicts. Islam gives freedom to humans to work such as: buying and selling, renting a lease, farming as well as entrepreneurship, etc. but must be avoided from vanity,To all parties that enter into a lease agreement - rent as far as possible and be able to implement the rules set by Islamic law.   Keywords: Lease-Rent Agreement, Islamic Law